Study on the Variation Law of Static Transmission Error for Cylindrical Gear - Chang Lehao; Liu Geng; He Zhaoxia (Jixie chuandong)
Based on a modified thin slice method,the static transmission error of cylindrical gear pair with tooth surface error is calculated efficiently. The transmission error is separated into composite deformation and composite mesh error,and the change of transmission error for gears with and without errors is studied. The results show that the transmission error of the ideal gear pair is related to the applied load and the theoretical contact length. Under the same loading condition,the transmission error will have local minimum fluctuations when the overlap（ or transverse） contact ratio is close to integers,while it will have local maximum fluctuations when the total contact ratio of a helical gear pair is close to integers. For a gear pair with tooth surface errors,the mesh stiffness,the composite mesh error and the actual contact length in a mesh cycle are similar to each other.The transmission error produced by gear errors is the crucial factor in light loading,while the tooth deformation becomes dominating in heavy loading. The conclusion can provide some references for the design of transmission error and vibration reduction of gear systems.